1992
DOI: 10.1177/002204269202200104
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Dimensions of Support for Decriminalizing Drugs

Abstract: This study uses surveys of citizens and criminal justice employees to illustrate the multidimensional nature of views about decriminalization. Both groups supported strict legal penalties for marijuana offenses and believed that if legal restrictions were eased other types of crime would increase. Ironically, they also expressed doubts about the effectiveness of the law. They believed that even if they had all the resources necessary the police could not stop marijuana use. At the same time they were willing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 11 publications
1
9
0
Order By: Relevance
“…As noted earlier, alcohol is viewed as a relatively "safe" drug that is associated with different attitudes and expectancies than other drugs are (Stylianou, 2002;Weisheit & Johnson, 1992). In the present study, we examined whether the relationship between substance use and relationship closeness is the same for LSD, a drug that is less socially acceptable than alcohol but still somewhat widely used.…”
Section: Relationship Closeness and Sexual Assaultmentioning
confidence: 83%
See 4 more Smart Citations
“…As noted earlier, alcohol is viewed as a relatively "safe" drug that is associated with different attitudes and expectancies than other drugs are (Stylianou, 2002;Weisheit & Johnson, 1992). In the present study, we examined whether the relationship between substance use and relationship closeness is the same for LSD, a drug that is less socially acceptable than alcohol but still somewhat widely used.…”
Section: Relationship Closeness and Sexual Assaultmentioning
confidence: 83%
“…For example, one largescale questionnaire study showed that over 55% of the respondents perceived the physical harm from alcohol and marijuana use to be comparable (Weisheit & Johnson, 1992), but this relatively receptive and accepting response differed distinctly from the responses given to drugs such as heroin, LSD, and cocaine. Over 84% of the survey respondents rated use of these substances as being more harmful than use of alcohol (Weisheit & Johnson, 1992). Another survey showed that, although most participants classified occasional use of LSD to be a serious crime, they merely "discouraged" the daily use of marijuana and alcohol (Stylianou, 2002).…”
Section: Substance Use and Sexual Assaultmentioning
confidence: 99%
See 3 more Smart Citations